Knowledge, attitude, and practices of midwives on premature rupture of membranes (PROM): A cross-sectional study in Samosir and Toba, Indonesia - Lumbanraja, Sarma N.; Tobing, Immanuel DL.; Santosa, Heru; Nasution, Mahyuddin KM.; Aritonang, Evawany Y.; Ichwan, Muhammad; Imelda, Fatwa; Siahaan, Andre MP. (Narra J, 2024)
Indonesia has a significantly higher maternal mortality ratio (MMR) than other countries in Southeast Asia, and infection is one of the most common causes of maternal deaths, of which premature rupture of membranes (PROM) can be the consequence of the infections. In primary healthcare settings, midwives play an important role in identifying and managing PROM appropriately; however, studies on their knowledge, attitudes, and practices related to PROM are limited. The aim of this study was to determine the midwives' knowledge, attitude and healthcare practice on PROM in Indonesia. A cross-sectional study was conducted among midwives at primary healthcare facilities in Samosir and Toba Regency, North Sumatra, Indonesia, from July to November 2022. The knowledge, attitude and practice towards PROM were assessed. Results showed that 57.5% of midwives had poor knowledge and 35.1% had poor attitude levels. There were 4.9% of midwives referred the patients immediately to the hospital. Our data indicated that aged 31−40 or 41−50 years, having a lower than bachelor degree and having a higher monthly number of referred PROM patients were significantly associated with poor knowledge compared to younger, having a bachelor degree, and lower monthly referral patient number, respectively. Similarly, younger, having higher degree and a having lower monthly referral number of PROM cases were associated with higher chances of having a sufficient-good attitude towards PROM. This study highlights that a significant percentage of midwives had poor levels of knowledge and attitude, and age, educational level and monthly referral number of PROM cases were associated with the level of knowledge and attitude.